2007
DOI: 10.1016/j.drugpo.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment uptake and outcomes among current and former injection drug users receiving directly observed therapy within a multidisciplinary group model for the treatment of hepatitis C virus infection

Abstract: Injection drug use accounts for the majority of incident and prevalent cases of hepatitis C virus (HCV) infection. However, very few injection drug users (IDUs) have received treatment for this condition given issues of medical or psychiatric co-morbidity, ongoing substance abuse and a widely held belief that such individuals will not be able to adhere to the requirements of therapy, including regular medical follow-up. With this in mind, we sought to evaluate HCV treatment uptake and outcomes among current an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 23 publications
2
99
2
1
Order By: Relevance
“…The finding of the feasibility of communitybased treatment provision to those who inject drugs is confirmed by another Canadian study conducted by Grebely et al 17 Community-based treatment provision to such individuals was through a multidisciplinary team model comprising both primary and secondary care clinicians. Of the participants, 65% achieved an end of treatment response (ETR) despite the fact that three-quarters of all recruited patients reported ongoing drug use.…”
Section: Qualitative Studiessupporting
confidence: 63%
See 1 more Smart Citation
“…The finding of the feasibility of communitybased treatment provision to those who inject drugs is confirmed by another Canadian study conducted by Grebely et al 17 Community-based treatment provision to such individuals was through a multidisciplinary team model comprising both primary and secondary care clinicians. Of the participants, 65% achieved an end of treatment response (ETR) despite the fact that three-quarters of all recruited patients reported ongoing drug use.…”
Section: Qualitative Studiessupporting
confidence: 63%
“…Several commentators have recommended that antiviral therapy can, and should, be delivered in the multidisciplinary primary care setting when focused on areas of high prevalence of HCV. 4,[8][9][10]15,17,[27][28] The findings of the current review have suggested that such primary care-based treatment is feasible with support from specialists. Such a model has treatment outcomes that are equivalent with secondary care services.…”
Section: Discussion Summarymentioning
confidence: 99%
“…Preliminary studies on treatment uptake indicate that willingness to enter treatment is high among active injectors (Grebely et al , 2007). Further, a recent review of treatment of active IDUs notes that treatment compliance and success rates are equal between active IDU and ex-or non-IDU (Hellard et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3 The literature offers several examples of successful models for delivering HCV care and treatment to active drug users. [4][5][6][7][8][9][10][11] We hope that this contradiction is resolved so that the Practice Guidelines are internally consistent in suggesting that clinicians broadly consider HCV treatment for active drug users in the context of supportive, multidisciplinary care.…”
Section: To the Editormentioning
confidence: 99%